Des besoins d'orientation au secondaires: nécessité de nouvelles stratégies d'éducation à la carrière - Dupont, Pierette; Gingras, Marcelle (Canadian Journal of Counselling and Psychotherapy, 2011)
Do the present practices in information and guidance truly meet the career education needs of the young? To answer this question, we have developed the Career Education Questionnaire. It is made up of three major parts: the first deals with the degree of importance and significance young people attach to work; the second part evaluates attitudes concerning career preparation; the third part evaluates students' knowledge of careers and the labour market. The questionnaire is administered to 1,022 last-year high-school students representing urban, semi-urban and rural areas. The results tend to confirm that changes are needed to meet more adequately the needs of the young.